2022
DOI: 10.1021/acsabm.2c00700
|View full text |Cite
|
Sign up to set email alerts
|

Directed Immobilization of PETase on Mesoporous Silica Enables Sustained Depolymerase Activity in Synthetic Wastewater Conditions

Abstract: Microplastic accumulation in terrestrial and aquatic environments is a growing environmental challenge. Biodegradation has shown promise as an intervention strategy for reducing the spread of microplastics. The wastewater treatment system is a key intervention point in microplastic biodegradation due to its pivotal role in the water cycle at the interface between human activity and the environmental. However, the best characterized microplastic degradation enzyme, PETase, lacks the stability to perform at scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…Therefore, there is a requirement to immobilize plastic-degrading enzymes on the surfaces of nanomaterials [ 79 ], especially on the surface of mesoporous silica by the sol–gel method [ 80 ]. Goddard et al reported [ 81 ] the direct immobilization of the enzyme on the surface of mesoporous silica by grafting the polyethylene terephthalate (PET) enzyme binding with a peptide (SBP), as shown in Figure 10 a. Furthermore, the introduction of PET enzyme-fixed mesoporous silica into the lining material of wastewater treatment tanks was found to enhance the degradation of microplastic waste ( Figure 10 b).…”
Section: Applications Of Mesoporous Silicamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a requirement to immobilize plastic-degrading enzymes on the surfaces of nanomaterials [ 79 ], especially on the surface of mesoporous silica by the sol–gel method [ 80 ]. Goddard et al reported [ 81 ] the direct immobilization of the enzyme on the surface of mesoporous silica by grafting the polyethylene terephthalate (PET) enzyme binding with a peptide (SBP), as shown in Figure 10 a. Furthermore, the introduction of PET enzyme-fixed mesoporous silica into the lining material of wastewater treatment tanks was found to enhance the degradation of microplastic waste ( Figure 10 b).…”
Section: Applications Of Mesoporous Silicamentioning
confidence: 99%
“… ( a ) The schematic illustration of the immobilization process of SBP-tagged PETase on mesoporous silica. ( b ) Proposed intervention of immobilized PETase for microplastic degradation in wastewater treatment tanks [ 81 ]. Copyright 2022, American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…In this regard, immobilization of Is PETase on Co 3 (PO 4 ) 2 nanoparticles has been shown to increase the enzyme lifetime by 75% [ 154 ]. Furthermore, the silica-immobilised PETase was successfully applied for wastewater treatment [ 154 , 155 ], whereas magnetic nanoparticles-tagged PETase was used for removal of PET microplastic [ 156 ]. Protein surface display represents another strategy for enzyme immobilisation, which is based on a functional display of target enzymes through fusion to various secreted proteins [ 59 , 123 , 124 , 127 , 129 ] ( Figure 3 ).…”
Section: Additional Approaches For Improving Enzymatic Pet Depolymeri...mentioning
confidence: 99%
“…Jia et al 29 immobilized IsPETase on a metal support by genetically fusing the enzyme to multiple histidine tags for metal binding, thereby increasing its stability. Additionally, Zurier et al 30 utilized genetic fusion of IsPETase with silica-binding peptides to immobilize the enzyme on silica nanoparticles, resulting in improved enzyme activity and stability. Chen et al 31 coimmobilized DuraPETase and MHETase in calcium phosphate nanocrystals (CaP) using the SpyTag/SpyCatcher system.…”
Section: Introductionmentioning
confidence: 99%